Study of Correlation of Hypertension and Anthropometric Measurements in Obese Vs Non – Obese Individuals (Academia Journal of Medicine, 2020)
Background: Obesity exists worldwide at a large incidence rate. All systolic and diastolic blood pressure show a strong association with the height and weight of both sexes. This research was intended to establish the incidence of hypertension in obese patients relative to findings reported in non-obese persons. The objective is to research Hypertension in accordance with the Body Mass Index and to equate it between the two classes of Obese and Non-Obese persons. Subjects and Methods: The following anthropometric tests were carried out of both such patients 1. Height 2. Weight 3. Circumference of dimension 4. The hip circumference. The Body Mass Index and the Waist Hip Ratio is determined from these measures. Blood pressure monitoring of BP was taken three times to validate systemic hypertension. Careful history was first taken of these cases involving pre-existing chronic hypertension and disease diagnosis. Results: The pre-hypertension level saw more people from both Obese and non-obese classes. Prevalence of stages 1 and 2 of hypertension was mostly seen in obese people. The mean systolic and diastolic blood pressure was higher in obese males than females but barely any noticeable variation in the waist circumference of > 100 and in the waist circumference of 90-100 cm, males were greater than females. Conclusion: The incidence of elevated blood pressure and mean systolic and diastolic blood pressure in increased BMI classes, i.e. obese people, was far higher. High BMI demonstrated a strong hypertension association.
Keywords: BMI; Hypertension; Obese; Waist circumference; Hip circumference